Pengaruh Remunerasi Dan Motivasi Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Surakarta) - Teja, Sri Gusti Bima Harya; , Prof. Dr. M. Wahyuddin, M.S; , Drs. M. FaridWajdi, M.M., Ph. D. (2017)
The purpose of this research is to analyze:1) remuneration influence on employee performance., 2) the effect of work motivation on employee performance. Data obtained from 86 respondents who are employees of BEA and excise Surakarta. The analytical method used is multiple linear regression. The test results of research instruments concluded that all the questions are valid and reliable for each variable. Classic assumption test shows that the normal distribution of data, linear, does not happen and does not happen heteroskedastisitas multikolinieritas. The results of this study show that: 1) remuneration positive and significant effect on employee performance, 2) work motivation positive and significant effect on employee performance